Sustainable forest management for nut and fuelwood production in the Jalalabad region, Kyrgyzstan: insights from local communities - Zhumasheva, Aidai; Han, Hee; You, Joung Won; Park, Pil Sun; Kang, Kyu-Suk (Frontiers in Forests and Global Change, 2024)
Jalalabad region in the Kyrgyz Republic is home to the world’s largest natural walnut (Juglans regia L.) forests and pistachio (Pistacia vera L.) forests. These nut-fruit forests serve as the primary source of income for local people; however, deforestation has led to a decline in the availability of these resources. Wood from the forest is also used as a crucial energy source for cooking and heating in this region, despite state protection of the walnut forest due to a lack of alternative energy sources. This study aimed to explore solutions to restore nut-fruit forests while providing a fuelwood source and improving the income of local people. Qualitative research methods were employed, including semi-structured interviews and survey questionnaires with farmers and central and local government officials. The study investigated the main environmental problem of forest degradation and the challenges of forest management, such as livestock and complicated lease arrangements, and determined possible government support and incentives for local communities to participate in forest rehabilitation, such as planting instead of paying lease fees. The findings indicated that a tree-based farming approach can be a promising alternative land-use solution. Seventy-four percent of local farmers expressed their readiness to plant fruit trees and fast-growing tree species to meet their demand for fuelwood and improve their livelihoods if the government can provide temporary fencing support. The study also highlighted the need for capacity building for farmers to learn proper planting, managing, and harvesting for more sustainable practices. Policymakers need to modify legislation through simplified and incentive-based forest lease arrangements.